The Effect Of Using Scattergories Learning Media On English Learning Outcomes Of Students In ClassV State Elementary School 098166 Perumnas 2025/2026 Academic Year - Haway Velita Sinaga; Imelda Sabrina Sibarani; Asister Fernando Siagian (PT. Padang Tekno Corp, 2025)
This research is focused on the effect of the use of scattergories learning media on the English learning outcomes of grade V students of SD Negeri 098166 Perumnas T.P 2025/2026. The purpose of this study is to determine the significant influence of the use of Scattergories learning media on the English learning outcomes of grade V students of SD Negeri 098166 Perumnas T.A 2025/2026.This researcher used a quantitative method with a pre-test-post-test one group design. The sample consisted of 24 students. Data was collected through pre-tests and post-tests in the form of written tests and analyzed using t-test formulas and N-gain tests. Based on the data, it was found that mastery of vocabulary in English and English learning outcomes were better after using scattergories learning media. This can be seen from the average score before treatment, which is 25.6 with the low category, after the treatment, which is 86 with the high category. Then there was a significant influence after using scattergories learning media on the English learning outcomes of grade V students of SD Negeri 098166 Perumnas. Based on the calculation of the N-gain test, the researcher found that the N-Gain test showed a value criterion of 0.7979 categorized as high classification.